Implementasi Moderasi Beragama Untuk Mencegah Konflik Sosial Melalui Dialog Lintas Iman - Umu; Abdul; Muhammad Shulthoni (Pascasarjana IAIN Metro, 2026)
Religious moderation has become a matter of great importance in Indonesia’s diverse and multicultural society, given that differences in belief can sometimes trigger social unrest. The practice of religious moderation through interfaith dialogue has emerged as an effective strategy for avoiding conflict, while upholding the values of tolerance, mutual respect, and finding common ground amid diversity. This study examines the implementation of religious moderation as a strategic approach to prevent social conflict by strengthening interfaith dialogue. The research employs a qualitative method based on an extensive literature review and descriptive analysis of various moderation practices implemented within educational institutions, government bodies, and religious communities. The findings reveal that religious moderation plays a crucial role in enhancing tolerance, mutual respect, and the community’s ability to manage diversity inclusively and constructively. Furthermore, interfaith dialogue has proven effective in creating safe and inclusive spaces for open communication, reducing prejudice, preventing radicalization, and mitigating potential horizontal conflicts. This study emphasizes that religious moderation and interfaith dialogue must be implemented in a synergistic manner through educational initiatives, policy development, and community empowerment as foundational efforts to strengthen social harmony.